Cancerous expansion of the city of Baghdad - Dr. Moheb Kamel Al-Rawe (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
If we look at the previous planning experiences in the failure to implement the basic plans for the city of Baghdad since its inception, and regardless of the extent to which these designs apply the foundations of correct and sustainable development, they were not facing problems related to the lack of planning laws for the foundations of development and the protection of resources, as was sometimes rumored as justifications for negligence, but they were It always contradicts the large expansion of slums, although they had not yet taken on their current dimensions, which were considered a reality despite all the "enforceable" laws as a result of the lack of resources necessary to implement these laws and despite all measures to adhere to these laws, they collided with the opposition, fraud, and justification. In slum areas. Among the positive indicators of these laws is that there has been a relative success in confronting the violations of building regulations in the planned areas. This relative success can be attributed to the possibility of imposing the law when the necessary will is available, and on the negative side lies in the imbalance in the treatment of slums according to the seriousness of their negative effects on natural resources, the environment, and the national economy.